OPTIMALISASI WEBSITE RUMAH SAKIT SEBAGAI SARANA EDUKASI KESEHATAN BAGI MASYARAKAT PEDESAAN - Lidya Paramitha Moha; Febrianti Mokodompis; Christiawati Sapii (Journal of Hulonthalo Service Society (JHSS), 2023)
Optimizing the hospital website is a strategic step in improving the quality of health of the village community through easily accessible education. This community service aims to provide information related to the benefits of the hospital website as a means of health education. This service activity was carried out in Tulabulo village, East Suwawa District, Gorontalo Regency. The method used is education and interactive discussions designed to provide an in-depth understanding of the importance of the hospital website as a means of health education. The results of the activity showed an increase in public knowledge about the use of the hospital website. This activity also identified the main obstacles of the community in the limitations of digital literacy and the lack of informative content relevant to the needs of the village community.